TRIAL OF ZEOLITE APPLICATION FOR WATER PURIFICATION UTILIZED IN CRUMB RUBBER PROCESSING - Rachmad Edison (Jurnal Zeolit Indonesia, 2007)
The research was conducted at laboratory of 2nd Crop Production, Lampung State Polytechnic using water added to zeolit in rubber processing and crumb rubber quality testing in PKST Kedaton. PTP Nusantara VII. The most important things in crumb rubber processing are water utilizing in latex dilution. Using lot of water in latex dilution can be straight away on rubber quality such as colour index, PRI, ash content, and dinginess content. The experiment was conducted on factorial method with completely randomized block design consist of two factors (4 x 5 with 3 replications. The first factor is water application (A) with A1 = well deep water, A2 = river water, A3 = fond water and A4 = latex serum. The second factors is dosage of zeolit (Z) with Z0 = without zeolit, Z1 = 2, 50%, Z2 = 5.00%, Z3 =10.00% and Z4 = 15.00% on water dilution. The result of the experiment showed that zeolit can increase pH and DHL of water, and rubber weight, but no effect on dinginess content, PO/PRI, and volatile matter. Zeolit application until 10.00% on latex serum can maintain the colour value of rubber and the other quality was not shown any different.